2019
DOI: 10.1002/jcp.28137
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol reverses promoting effect of the HOTAIR/miR‐124/Notch1 axis on renal interstitial fibrosis in a rat model

Abstract: Renal interstitial fibrosis (RIF) is a common manifestation of inflammatory and noninflammatory renal diseases, which correlates to renal excretory dysfunction. Recently, the long noncoding RNAs (lncRNAs) have been demonstrated to be involved in the development of various renal diseases. Here, we aim to determine whether paeonol (PAE) affects RIF with involvement of the lncRNA HOX transcript antisense intergenic RNA (HOTAIR)/microRNA‐124 (miR‐124)/Notch1 axis. RIF rat models were established by performing unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…S7). IMR-1 evidently can inhibit Notch signaling at higher concentrations, as previously reported (30,59,60). RIN1 is another small molecule that was recently reported to modulate the Notch transcription complex (31).…”
Section: Discussionsupporting
confidence: 55%
“…S7). IMR-1 evidently can inhibit Notch signaling at higher concentrations, as previously reported (30,59,60). RIN1 is another small molecule that was recently reported to modulate the Notch transcription complex (31).…”
Section: Discussionsupporting
confidence: 55%
“…LncRNA HOX transcript antisense RNA (HOTAIR) has been found to promote hypoxia-induced ischaemic infarct (Yang and Lu, 2016). A previous report indicated that PAN inhibited the expression of HOTAIR (Zhou et al, 2019). Thus, PAN might affect the progression of ICH via regulation of HOTAIR.…”
Section: Introductionmentioning
confidence: 99%
“…The decreased DE miRNAs with the largest numbers of targets included miR-122-5p, the miR-3073 family (miR-3073a-5p, miR-3073a-3p and miR-3073b-5p), the miR-1948 family (miR-1948-5p and miR-1948-3p), miR-669c-5p and let7a-1-3p. Among these, fibrosis was reported to be regulated by the increase in expression of the miR-21 family ( 49 54 ), miR-124 family ( 55 , 56 ) and miR-34b-3p ( 57 , 58 ), and the decrease in miR-122-5p ( 59 61 ) and let7a-1-3p ( 62 ). The present study was the first to report that AAN was associated with an increase in miR-129-2-3p expression and a decrease in the expression levels of the miR-3073 family (miR-3073a-5p, miR-3073a-3p and miR-3073b-5p), miR-1948 family (miR-1948-5p and miR-1948-3p) and miR-669c-5p.…”
Section: Discussionmentioning
confidence: 99%